Optimization extraction of rosemary essential oils using hydrodistillation with extraction kinetics analysis - Hanyue Chen (Wiley, 2021)
Abstract Rosemary (Rosmarinus officinales L. (Labiatae)) is one of the major economic crops in the world, and rosemary essential oil (REO) is one of the top products derived from rosemary and has excellent commercial prospects. Many factors affect the yield of REO extracted by hydrodistillation (HY). This study was proposed to identify and analyze these factors to maximize the yield of essential oils and reduce the cost. First, two different single‐factor extraction experiments were conducted, (1) adding NaCl and (2) using various organs of the plant, to determine the influence of each factor on the oil yield. Based on single‐factor experiments, the orthogonal experiments (L9, 33) were designed to determine the optimal conditions for the extraction of rosemary oil. Meanwhile, the kinetic extraction analysis of the test data was carried out. The results revealed that the highest oil yield was achieved when rosemary leaves were crushed to 2 cm, the ratio of water to the material was 1:3, and NaCl concentration was 5%. A simple first‐order kinetic model has also proved to be an acceptable general choice and allows to predict the output of extraction operations overtime accurately and robustly in practice. This study provides a reference scheme for using hydrodistillation to extract rosemary essential oil.